(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Sports are understood as one of the dynamic forces in developing national integrity among the masses creatingnational unity in the country; where as sports diplomacy is referred when sport is used as a political means to improverelations and some times may worsen diplomatic relations between two nations. The intention is to bring about fundamental changes relating to fine relations. While the Olympics events are the leading political examples of usingsports for diplomatic means, such as cricket, table tennis and football as well as other international sports competitionshave also been used in this regard. In the case of Apartheid, competitive sport was used to isolate South Africa thatbrought major changes in nation’s social structure in terms of socio- political relationship, examining the sportsdiplomacy that adopted by Nelson Mandela of South Africa, and Irans former President Khatami’s inspiring initiative provided an opening for a watchful rapprochement policy with USA, advocating people-to-people contacts betweenthese two nations to release tensions developed between them that may be compared with ping pong diplomacy,which softened US-Chinese relations.